(untitled) (Educational Dimension, 2021)
The current state of higher education is characterized by significant reforms. The state needs highly qualified specialists with professional competencies and a well-established system of moral attitudes and beliefs. That is why the issue of training, which includes the education of the personality of students in higher education, is relevant at this stage of development of education in Ukraine. The article highlights the goals of professional training, urgent tasks that arise in modern education. The need to build a model of the education system as an effective means of achieving goals and solving problems is emphasized. The article considers approaches to the definition of “model”, “modeling”. The classification of models is presented. Yes, scientists distinguish between physical, mathematical, computer, descriptive models. They are also divided into educational and research. The latter can be ascertaining, research, imitation. It is determined that the humanities prefer descriptive and mathematical models. Important requirements for the models include adequate reflection of characteristics and reliability. Pedagogical modeling is considered as a method of pedagogical research, which allows to increase the efficiency of the educational process, as well as aims at educators to implement the tasks of personality-oriented learning. The stages of modeling of the educational system (cognitive-analytical and constructive) and its activity during each of them are analyzed, in particular definition of the purpose, tasks, substantiation of pedagogical conditions, realization of psychological and pedagogical diagnostics, forecasting of results of activity, definition of forms, methods, methods of work, educational tools. The article reviews the models of the training system proposed by domestic scientists. It is determined that the main components of the model are: purpose, stages, pedagogical conditions, functions, forms, methods of work and result. It was found that the effectiveness of the implementation of the model is possible provided the unity and indivisibility of all its components. We consider the implementation of a comparative analysis of the training system models of Ukraine and Western countries to be a prospect for further research.